(untitled) (Bangladesh Journal of Plant Taxonomy, 2024)
Globba zwegabinensis sp. nov., under sect. Haplanthera (Zingiberaceae) is newly described and illustrated from the Zwegabin Mountain of Kayin State in southern Myanmar. G. zwegabinensis is morphologically allied to G. sessiliflora and G. lithophila but differs in having the leaves with a foetid smell, glabrous blade, completely yellow filament, glabrous ovary, larger cuneiform labellum with bifid apex, glabrous and oblong to ovate fruit, lack of bulbils and anther appendages. A description and photographic data, along with the comparative characteristics of the closely allied species, are provided. Bangladesh J. Plant Taxon. 31(2): 197-203, 2024 (December)